O programa IFS sustentável diante do Estado de Direito Socioambiental: desafios e perspectivas - Santos, Necéssio Adriano (2017)
The present work aims to build an analysis of the performance of the Sustainable IFS Program in the Campus Aracaju of the Federal Institute of Sergipe, under the perspective of the State of Social and Environmental Law, relating it to the challenges and perspectives in the implementation and development of the project, with the Generate information to encourage the improvement of the program. The Sustainable IFS Program was created by Ordinance No. 1,337 of June 5, 2014, representing an institutional commitment in defense of the environment, with a view to contributing to the development of sustainable values in the academic community. It is based on the question that with the implementation of the Sustainable IFS program, which aims to contribute to reducing the use of resources and minimizing the environmental impacts caused by the various activities within the IFS, there will be a significant reduction of these problems and Improvement in the other areas of action of the Program, which are: Environmental Education; Sustainable Tenders; Quality of Life in the Work Environment; Awareness and Training of Teachers, Technical-Administrative, Students and Collaborators; Rational Use of Resources; And Sustainable Construction. The methodology used was based on a qualitative approach through the participant research that had as a locus of research the Campus Aracaju of the IFS, use of the documentary and bibliographic analysis. Emphasis was placed on Environmental Education, with a curricular analysis in terms of curricular and / or cross-curricular forecasting of the environmental theme, as well as outlining the profile of higher education students to subsidize possible actions in the environmental theme in a way directed to the socioenvironmental context of the Actors involved. The results showed that although the Sustainable IFS Program is still in the implantation phase, there are several isolated actions in the Aracaju Campus in all the guiding axes of the program, many of them starting from the rectory itself and not directly from the campus. Regarding the analysis of the Pedagogical Projects of the Courses, it was verified that all of the higher courses of the Campus have specific subjects with the environmental theme. In relation to the forecast of use crossdisciplinary between the subjects, or of prediction expressed in the objectives of the course or in the profile of the egress, with the exception of the Degree in Mathematics, all courses have the express forecast of the use of socio-environmental ethics as parameter For professional training.